ANALISIS FAKTOR PENYEBAB PESERTA DIDIK MEROKOK DI KELAS VIII SMP NEGERI 6 PONTIANAK - Jaka Alfa Abet Nego; Indri Astuti; Yuline Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe purpose of education is to develop the potential of students to become human beings who have faith and are devoted to God Almighty, have good character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens. However, observations show that there are students in SMP Negeri 6 Pontianak who smoke in the school canteen and when they come home from school. The method used is descriptive method and the form of research is survey research. This research uses a qualitative approach. Data collection techniques used were interviews, observation, and documentation. Based on the results and discussion of the study, the internal factors causing students to smoke are; (1) want to be accepted by the group, (2) want to show self-identity, (3) want to know the taste of cigarettes, and external factors causing students to smoke namely; (1) smoking family environment (2) school friends who smoke, and (3) the majority of smokers. So, the conclusions of the factors causing smoking students are; (1) want to be accepted by the group, (2) want to show self-identity, (3) want to know the taste of cigarettes, (4) smoking family environment, (5) classmates who smoke, and (6) the majority of smokers.Keywords: Students, Causes, Smoking